CUIDADOS DE ENFERMAGEM ONCOLÓGICA HUMANIZADOS - Paulo Alexandre Oliveira Marques; Ana Sofia Magalhães Lopes; Ana Lúcia Barbosa Ribeiro; Daniela Francisca de Oliveira Santos (Cogitare Enfermagem)
Editorial.